PRACTICING ENTREPRENEURIAL LEARNING AS LEARNING METHOD AT MIDDLE SCHOOL STUDENTS - Widyo Pebruanto, Dwi Sunu; Hashim, Norashidah Binti; Hashim, Rosna Bt. Awang (Jurnal Entrepreneur dan Entrepreneurship, 2018)
Entrepreneurship education as method needs further exploration in the context of school. Entrepreneurship Center of Ciputra University collaborated with a number of schools in Indonesia developed the K-12, Ciputra Way Learning Cycle. As many as 355 final year students from six schools were involved in this study to gain better understanding towards the factors influencing entrepreneurial competences. Using the method of Structural Equation Model (SEM), result shows that growth orientation, assessment for improvement, positively influence entrepreneurial competences.